Enhanced DC Microgrid Protection: a Neural Network and Wavelet Transform Approach - El Gohary, Youssef Hesham (2024)
A Master of Science thesis in Electrical Engineering by Youssef Hesham El Gohary entitled, “Enhanced DC Microgrid Protection: a Neural Network and Wavelet Transform Approach”, submitted in May 2024. Thesis advisor is Dr. Ahmed Osman. Soft copy is available (Thesis, Completion Certificate, Approval Signatures, and AUS Archives Consent Form).